Canadian Federalism, Indigenous-state Relations, and the Algonquin Land Claim - Jenna L. Davidson (Canadian Planning and Policy, 2022)
The Algonquin Land Claim negotiations have been ongoing for over 25 years in Ontario and will be the province’s first modern-day constitutionally protected treaty. Traditional territories of the Algonquin Anishinaabeg under claim include areas in the Ottawa River Valley and the City of Ottawa itself. As a result, this land claim is unique in jurisdictional complexity, situated in urban landscapes that are heavily populated and developed, as well as rural areas that feature cottage country, hunting and fishing camps, provincial parks and natural resource projects. To answer the question: what is the process for negotiating lands for transfer to Indigenous communities within urban and rural contexts? This research investigates the Algonquin Land Claim case study within Canada’s current jurisprudential landscape of Indigenous sovereignty and recognition, and the implications it has for land use planning in Ontario. As a practical profession operating within relationships between Indigenous and non-Indigenous communities, the study explores planning practices in the context of negotiating a modern-day treaty. This recount of Canada’s legislative history and its interaction with Indigenous nations infuses many references to the fundamental attributes of Canadian federalism, Indigenous jurisdiction and the tensions that lie between the two concepts.